Synthesis and Characterization of Simulated Corium Materials - Ozolins, Jesper (My University, 2025)
One part, of the massive undertaking that is risk management and accident prevention regarding nuclear power, is the study of corium. Corium, being the resulting material created during a nuclear meltdown, is an amalgamation of molten nuclear fuel combined with anything and everything it comes into contact with. Corium is not only dangerous during a meltdown when it risks causing further damage to the reactor and surrounding equipment. Due to it’s high radioactivity, it stays dangerous for a significant amount of time after the accident as well. It is therefore important to study this material in order to better understand how to minimize any potential further damage, further contamination of surroundings and to find ways to safely carry out cleanup efforts. These studies however, are quite limited due to the hazardous nature of the corium. This project is therefore focused on exploring a way to safely synthesize small batches of low-activity corium, without requiring specialized equipment, to be used for smaller scale studies. This proof of conept was achieved by first synthesizing spent nuclear fuel consisting of UO2 in the form of 238 U, as a lower activity replacement of enriched uranium, doped with several inactive elements for the purpose of simulating fission products. This powdered SIMfuel was then ground together with a selection of materials commonly found on the inside of a nuclear reactor and then fired in a reducing atmosphere at temperatures up to 1750℃ to create a clump of material similar to corium. Analysis of this corium using powder-XRD and ICP-MS showed that the structure and properties of the synthesized corium varies significantly based on the composition and temperature it was created in. A leaching study was also carried out using the samples, but the results were inconclusive. The (justifiable) lack of real-world corium samples available for analysis means very little to compare these samples to, but this shows that a method of creating low activity samples it possible.